Investigating the Situation for Children with Autism and Their Families in Cambodia - Richard Rose; Bhoomikumar Jegannathan; Dalin Mong; Puthy Pat; Derozet Sok (MDPI AG, 2023)
Following periods of conflict and instability during the oppressive regime of the Khmer Rouge (1975-1978) and the period of Vietnamese occupation (1978-1992), the Kingdom of Cambodia has adopted policies and initiatives that aim to ensure greater equity and stability across all services in the country as a signatory to international agreements for the promotion of universal primary education (United Nations 2015). The education of children with disabilities continues to present challenges to both policy makers and service providers in Cambodia, though government agencies have made a commitment and invested resources to improve facilities and increase awareness of the difficulties experienced by children and families. Previous studies of provision for children on the autism spectrum in Cambodia suggest that they are little understood and that many experience difficulties accessing appropriate services or support. However, these reports have often been based on localised small-scale studies and have not provided a broader national perspective of the situation. A national analysis of the situation for persons with autism was conducted to provide a more detailed picture of the experiences of children with autistic spectrum disorders and their families. Data were collated using focus groups and interviews with service users and providers from a purposive stratified sample across the country. The findings reveal that a limited awareness and understanding of autism amongst both professionals and the general public has limited opportunities for development. Education facilities and expertise are limited, and access to therapeutic and specialist medical provision is poor. The pervasive nature of poverty has been a major contributory factor in the slow development of and accessibility to services to this population. A number of recommendations have been made and are being used to shape future policies for children with autism and their families in Cambodia.